Nanobodies for accurate recognition of iso-tenuazonic acid and development of sensitive immunoassay for contaminant detection in foods. (June 2022) - Wang, Feng; Yang, Yuan-Yuan; Wan, De-Bin; Li, Jia-Dong; Liang, Yi-Fan; Li, Zhen-Feng; Shen, Yu-Dong; Xu, Zhen-Lin; Yang, Jin-Yi; Wang, Hong; Gettemans, Jan; Hammock, Bruce D.; et al.
Abstract: The accurate analysis of chemical isomers plays an important role in the study of their different toxic effects and targeted detection of pollutant isomers in foods. The Alternaria mycotoxins tenuazonic acid (TeA) and iso-tenuazonic acid (ITeA) are two isomer mycotoxins with the lack of single analysis methods due to the similar structures. Antibody-based immunoassays exhibit high sensitivity and superior application in isomer-specific determination. Previously, various kinds of antibodies for TeA have been prepared in our group. Herein, highly specific nanobodies (Nbs) against ITeA mycotoxin were selected from immune nanobody phage display library, and one of Nbs, namely Nb(B3G3) exhibited excellent affinity, thermal stability as well as organic solvent tolerance. By molecular simulation and docking technology, it was found that stronger interaction between Nb(B3G3) and ITeA lead to higher affinity than that for its isomer TeA. Furthermore, a sensitive indirect competitive enzyme-linked immunosorbent assay (icELISA) was established with a limit of detection (LOD) of 0.09 ng/mL for ITeA mycotoxin. The recovery rate of ITeA in spiked samples was analyzed with 84.8%–89.5% for rice, 78.3%–96.3% for flour, and 79.5%–90.7% for bread. A conventional LC-MS/MS method was used to evaluate the accuracy of this proposed icELISA, which showed a satisfactory consistent correlation. Since the convenient strategy for nanobody generation by phage display technology, this study provide new biorecognition elements and sensitive immunoassay for analysis of ITeA in foods. Graphical abstract: Image 1 Highlights: Isomer-specific nanobodies for Alternaria mycotoxin iso-tenuazonic acid (ITeA) were selected from immune nanobody library. The unique nanobody Nb(B3G3) exhibited excellent affinity, thermal stability and organic solvent tolerance. The mechanism of accurate recognition of Nb(B3G3) and ITeA was illustrated by molecular simulation and docking technology. A sensitive icELISA was established with the LOD of 0.09 ng/mL for ITeA.